Bighorn sheep - Borgert-Spaniol, Megan, 1989- (Blastoff! readers. North American animals., 2016)
"Simple text and full-color photography introduce beginning readers to bighorn sheep. Developed by literacy experts for students in kindergarten through third grade"--